Electrically conducting films prepared from graphite and lignin in pure water - Suzuki, Asami; Otsuka, Yuichiro; Shikinaka, Kazuhiro (Frontiers in Bioengineering and Biotechnology, 2022)
In this paper, we present the electrically conducting self-standing graphite films consisting of lignin derivatives extracted by simultaneous enzymatic saccharification and comminution (SESC). Sonication of graphite powder in the presence of SESC lignin and pure water gave a water dispersion of SESC lignin-attached graphite without the need to add other chemicals. The SESC lignin-attached graphite with a diameter of several micrometres can be used as surface electro-conductive coating and molded into self-standing films by drying its water dispersion. SESC lignin-attached graphite film exhibits higher conductivity (~ 2075 S/cm) relative to graphite-based composites consisting of ordinary lignin derivatives. Manufacturing to self-standing film of micrometer-sized graphite by the SESC lignin would make the film of SESC lignin-attached graphite highly electrically conducting nature. The size of SESC lignin-attached graphite is proportional to conductivity of films. The SESC lignin-attached graphite also acts as an anti-plasticizer and as a conductive filler for polymer films, i.e., conductive films consisting of poly(ethylene glycol) or Li+ montmorillonite can be obtained via a water-based process.